DETERMINATION OF RADON CONCENTRATIONS IN DWELLING IN ACEH - Wahyudi Wahyudi; Dadong Iskandar; Rini Safitri; Kusdiana Kusdiana (Universitas Syiah Kuala, 2017)
Abstract. Determination of radon concentrations in dwelling in Aceh region by using a passive method has been conducted. In this research, area considered was divided into several sections called grid. Each grid represents an area of 60 km x 60 km in which, depend on public response, 6-10 passive radon monitors were installed. The number of passive radon monitors installed in Aceh is 200 units, and they can be taken back as many as 191 units or 95.50 %. The passive radon monitors have stayed in dwelling for 3-4 months and after period of the exposure, those radon monitors were taken back and brought to laboratory for further process, and then the track were read and the radon concentrations were calculated. Furthermore, data of radon concentration in dwelling and GPS location were put into MapInfo Software v.10.5 to create a map of radon concentration. The results of the analysis of the radon concentration in dwelling in Aceh demonstrate that the concentrations are in the range of 3.32 ± 0.23 Bq/m3 up to 68.30 ± 4.83 Bq/m3. This result was lower than the radon reference level determined by UNSCEAR, which was 300 Bq/m3. The data are useful in the regional extension and development plans, as well as the basis for health policy analysis due to the existence of radon in Indonesia. Furthermore, these data will become the contribution of Indonesia in the international world through UNSCEAR, IAEA and WHO. The data obtained can be used as partial data in creating a map of radon concentration in residents’ houses in Aceh, as a part of the map of radon concentration in Indonesia. Keywords: radon concentration, dwelling, Aceh, passive methodREFERENSI UNSCEAR, 1996, Natural Radiation Exposures, Forty Fifth Session, VienaIAEA, 2005, Radiation, People and the Environment, Viena.Bunawas, Emlinarti, M. Affandi, 1996, Penentuan laju lepasan radon dari bahan bangunan menggunakan metode pasip dengan metode jejak nuklir, Prosiding PPIKRL, PSPKR-BATAN, 20-21 Agustus 1996, pp. 16-21.Sutarman, L. Nirwani, Emlinarti dan A. Warsona, 2005, Penentuan konsentrasi gas radon dan thoron menggunakan detektor film LR-115 di DKI Jakarta dan sekitarnya, Prosiding PPI–PDIPTN P3TM-BATAN, Jogjakarta, p. 212-221.M. Affandi, D. Iskandar, dan Bunawas, 1996, Radon di Kompleks Perumahan BATAN, Presiding PIKRL, PSPKR-BATAN, p. 262-265Wahyudi, Kusdiana and D. Iskandar, 2016, Mapping of Indoor Radon Concentration in Houses Located in South Sulawesi Province, 2nd International Conference on the SERIR2 14th Biennial Conference of the SPERA, Bali, CTRSM-BATAN, p. 35-38.E. Pudjadi, Wahyudi, A. Warsona and Syarbaini, 2016, Measurement of Indoor Radon-Thoron Concentration in Dwellings of Bali Island, Indonesia, 2nd International Conference on the SERIR2 14th Biennial Conference of the SPERA, Bali, CTRSM-BATAN, p. 186-192.M.H.Magalhães, et al., 2003. Radon-222 in Brazil: an outline of indoor and outdoor measurements. Journal of Environmental Radioactivity, 67(2), pp.131–143.F.S. Al-Saleh, 2007. Measurements of indoor gamma radiation and radon concentrations in dwellings of Riyadh city, Saudi Arabia. Applied Radiation and Isotopes, 65(7), pp.843–848.